The food habits of Greylag and Barheaded Geese in the Keoladeo National Park, India - Middleton, Beth A; van der Valk, A. G. (Wildfowl, 1987)
The food habits of overwhelming Greylag Anser anser rubrirostris and Barheaded Anser indicus Geese were investigated in the Keoladeo National Park, Bharatpur, India. Greylag Geese eat mostly seeds of Nymphaea nouchali and Oryza rufipogon in November and December but shift to native grasses such as Paspalum distichum in January. They eat mostly P. distichum until they leave in March. Barheaded Geese eat mostly young wheat in January, native grasses, such as P. distichum in February and change to field peas and grams in March and April. Native wetland plants make up most of the diet of Greylag and Barheaded Geese, 100% and 52% respectively. Overall, P. distichum is the most important species in the diet of these geese, comprising 67.8% of the Greylag and 45.4% of the Barheaded Goose diet.